2020
DOI: 10.4174/astr.2020.98.4.199
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of minute T1 colorectal cancer in relevance to pathology and treatment

Abstract: Purpose: Minute T1 colorectal cancer (CRC) lesions (≤5 mm) are rare; however, little is known about their characteristics and aggressiveness. In this study, we evaluated the characteristics of minute T1 CRC in relevance to pathology and treatment. Methods: This retrospective study included 849 patients with T1 CRC endoscopically or surgically treated between January 2001 and December 2016. The patients were stratified into 4 groups according to tumor size; minute group (≤5 mm), small group (6-10 mm), medium gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In Park et al [38] research in CRC, they suggest TOMM20 as a potential therapeutic target of CRC. Yang et al [39] found overexperssion of TOMM20 which impacted liver cancer prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…In Park et al [38] research in CRC, they suggest TOMM20 as a potential therapeutic target of CRC. Yang et al [39] found overexperssion of TOMM20 which impacted liver cancer prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation limit of lesion size in CSP is because of its en-block resection ability [ 3 , 4 ] and the low frequency of carcinomas. Although the proportion of colorectal cancer in colorectal neoplastic lesions measuring less than 10 mm is thought to be very low, there are lesions with an advanced histology regardless of their small size [ 5 ]. Dye-assisted magnifying colonoscopy and image enhancement have high diagnostic accuracy for not only differentiating neoplastic and non-neoplastic lesions but also for the prediction of invasion depth in submucosal cancers [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cold snare polypectomy (CSP) is a well-established method for the resection of colorectal polyps measuring less than 10 mm, as it is associated with a low frequency of post-procedural bleeding and perforation [ 3 , 4 ]. Although the proportion of malignancy in colorectal neoplastic lesions measuring less than 10 mm is considered very low, small lesions with advanced histology have been reported [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive predictive value of some of these risk factors, such as depth of invasion, is suboptimal and can lead to a high proportion of unnecessary surgeries. The result is that LNM are found in only 10-20% of cases that undergo additional surgical resection after an initial local T1 CRC resection [5][6][7][8]. This means that 80-90% of these patients are exposed to the risks and sequelae of major surgery without any benefit other than confirming the otherwise unlikely absence of regional nodal tumor spread.…”
Section: Introductionmentioning
confidence: 99%